Leadership Innovation in Building an Adaptive Organization Case Study of Transformation in the Nahdlatul Ulama Sidoarjo Branch Management - Moch. Zakki Mubarok; Zaid Al Qodhi (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2024)
This research delineates the role of leadership innovation in transforming the Nahdlatul Ulama Branch Board in Sidoarjo into a more adaptive organization. Employing qualitative methods, the study analyzes the impact of leadership innovation on organizational transformation. The results indicate that the adoption of leadership innovation, including the implementation of new strategies and the development of leader-ship skills, significantly expedites the organizational adaptation process to external changes. Leadership innovation in the context of the Management Board of Nahdlatul Ulama Sidoarjo not only involves the introduction of new technologies and working methods but also entails a change in organizational culture. These findings are consistent with modern leadership theories, emphasizing the importance of cultural transformation to achieve sustainable adaptability. This research provides profound insights into how leadership innovation can be pivotal in addressing contemporary challenges, particularly in the realm of religious organizations. Practical implications include guidance for leaders in similar organizations, em-phasizing the significance of innovation in attaining the necessary adaptability in an era marked by dyna-mism and complexity. Keywords : Adaptive Organization, Leadership Innovation, Leadership Skills, Nahdlatul Ulama, Organizational Transformation.